151k views
1 vote
Let m = 6x +5.
Which equation is equivalent to (6x + 5)^2 – 10 = -18x – 15 in terms of m?

User Xjasz
by
5.0k points

1 Answer

3 votes

Answer: m² + 3m - 10 = 0

Explanation:

From the expression, considering

6x + 5 = m

The original expression

( 6x + 5 )² - 10 = -18 - 15

Factorize the right hand expression,

-18 - 15 = -3( 6x - 15 )

Since m = 6x + 5 , we now substitute for m in that expression

m² - 10 = -3m

Now re arrange the equation in the form,

ax² - bx + c = 0

Now back to the equation,

m² + 3m - 10 = 0,

So the equivalent equation will be

m² + 3m - 10 = 0

User Phluks
by
5.4k points